ACCURACY OF SELF-REPORTED HEIGHT, BODY MASS AND DERIVED BODY MASS INDEX IN A GROUP OF LAW ENFORCEMENT OFFICERS - Dawes, J. Jay (NBP. Nauka, bezbednosti, policija, 2019)
Height and body mass data is often self-reported by study participants. However, the accuracy of self-reported height and body mass data compared to these same measures collected by researchers is unknown. The purpose of this study was to compare the accuracy of self-reported height and body mass data to measured values within a law enforcement population, and the impact these estimations have an the accuracy of  BMI classifications. METHODS: Self-reported and measured height and body mass data for thirty-three (n = 33) male law enforcement officers (age: 40.48 ± 6.66 yrs; measured height: 180.42 ± 6.87 cm; measured body mass: 100.82 ± 19.86 kg) were utilized for this analysis. RESULTS: Paired samples t-tests revealed no significant differences in estimated and measured height (p=.830), body mass (p = .527) or BMI (p = .623). CONCLUSION: Self-reported height and body mass was accurate for calculating BMI within this population sample.